Modern architecture a very short introduction - Sharr, Adam ca. 20./21. Jh (Oxford University Press, 2018)
Adam Sharr tells the story of how modern architecture developed and produced its powerful cultural images. Considering the new building materials and techniques which shaped the movement, such as innovations in steel and concrete and the advent of air conditioning, he concludes by asking whether contemporary architecture remains modern at heart
Previously issued in print: 2018. - Includes bibliographical references and index
Keywords: Geschichte 1910-1970; Architecture, Modern; Moderne; Stahl; Licht; Luft; Architektur; Eisen